Contact Geometry and Pathway Determined Carriers Transport through Microscale Perovskite Crystals. Issue 9 (15th February 2023) - Zhao, Zhibin; Li, Yuelong; Ni, Lifa; Nam, Jongwoo; Adijiang, Adila; Zhang, Xubin; Li, Shanshan; Wang, Mingwei; Lee, Takhee; Xiang, Dong
Abstract: With the miniaturization of crystals‐based photoelectric devices, electrode contact‐geometries may play a critical role in determining the device performance. However, investigation of the role of electrode contact geometries in situ faces great challenges due to the electrode contact geometry is typically unmodifiable. To this end, a kind of liquid metal is employed as an adaptive‐deformable electrode to study the carrier transport through perovskite microcrystals, in which the electrode contacts geometries/positions and thus the carrier‐pathways can be adjusted. Under light illumination, a spike feature of photocurrent is observed when carriers transport along the perovskite microcrystal surface upon an edge‐contact geometry, which is absent as the carrier mainly transport through crystal interior upon a top‐contact geometry. Switching, rectifying, and memristor functions are selectively realized just by modifying the contact geometry. The underlying mechanism for the observations is further elucidated. This study provides a platform for studying carrier transport through microscale crystals with adjustable contact geometry and supplies an approach for fabricating diverse functional devices by changing the electrode contact‐geometries. Abstract : By employing a deformable liquid metal electrode, it is demonstrated that the carrier‐pathway not only affects the carrier generation/recombination and trapping/detrapping process but also strongly influences the conductive filament formation in perovskite microcrystals, providing an approach for fabricating functional devices via the control of contact geometry.